Ferritic stainless steel welding wire resistant to high-temperature molten salt-liquid Cd corrosion and application

By using high-temperature molten salt-liquid Cd corrosion ferrite stainless steel welding wire, combined with tungsten argon arc welding and high-purity argon protection, the corrosion resistance and mechanical properties of spent fuel dry post-treatment electrolytic refining/extraction container welding joints in high temperature and corrosion environments are solved, and stable welding effect with few defects and excellent performance indicators are achieved.

CN119733988AActive Publication Date: 2025-04-01INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510165113.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-01
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

The spent fuel dry-process electrolytic refining/extraction container is difficult to meet the requirements in high temperature and corrosion environments, and the existing technology lacks mature material selection and welding technology.

Method used

High-temperature molten salt-liquid Cd corrosion ferrite stainless steel welding wire is used. The chemical components of the welding wire include Si, Ti, Cr, Mo and other elements. It is produced by smelting and producing through vacuum induction furnace or electric furnace. The tungsten argon arc welding method is used during welding, and high-purity argon gas is used for arc protection.

Benefits of technology

The simplicity and feasibility of the welding process are achieved. The weld has excellent resistance to molten salt corrosion and liquid Cd corrosion at 550℃, and its mechanical properties also meet design indicators, including yield strength, tensile strength and impact toughness at room temperature and high temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733988A_ABST
    Figure CN119733988A_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature molten salt-liquid Cd corrosion resistant ferritic stainless steel welding wire and application, the welding wire is suitable for welding of spent fuel dry post-treatment electrolytic refining / extraction containers, and the welding wire belongs to the technical field of metal materials (welding materials). The welding wire comprises the following chemical components in percentage by weight: less than 0.05 percent of C, 1.5 to 2.5 percent of Si, 0.1 to 0.7 percent of Ti, 0.02 to 0.07 percent of C + N, 0.2 to 0.6 percent of Al, 15.5 to 18.5 percent of Cr, 0.2 to 0.6 percent of Mo and the balance of Fe and inevitable impurity elements. A welding seam obtained through welding of the welding wire has excellent high-temperature molten salt corrosion resistance and liquid Cd corrosion resistance. And meanwhile, the high-temperature molten salt-liquid Cd welding flux-cored wire further has high strength and toughness and is suitable for welding of dry-process post-treatment spent fuel electrolytic refining / extraction containers, and the service safety of the high-temperature molten salt-liquid Cd welding flux-cored wire in the high-temperature molten salt-liquid Cd complex corrosion environment is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials (welding materials), and in particular to a ferrite stainless steel welding wire resistant to high temperature molten salt-liquid Cd corrosion. The welding wire is suitable for welding spent fuel dry post-processing electrolytic refining / extraction containers. Background Art

[0002] With the support of closed fuel cycle, the utilization rate of uranium resources of integrated fast reactor can be increased from 1% of pressurized water reactor to more than 60%. Dry reprocessing technology is the key link of closed fuel cycle of integrated fast reactor, and it is also the realistic technical choice of closed fuel cycle. It is the only feasible technology to solve the problem of uranium resource supply and nuclear waste treatment. Electrolytic refining / extraction in dry reprocessing technology is the key link to realize the recycling of uranium and transuranic elements in spent fuel. This link is carried out in electrolytic refining / extraction container, but it is in the harsh and complex environment of high temperature (550℃) and corrosion (molten chloride salt-liquid Cd coupling environment) for a long time, which makes the mechanical and corrosion resistance of transuranic electrolytic refining / extraction container parts and their welded joints face huge challenges. At present, there is no mature material selection experience for such equipment worldwide. The research and development of related materials and technologies is one of the limiting links for the engineering and industrialization of dry reprocessing technology. Summary of the invention

[0003] The present invention relates to the technical field of metal materials (welding materials), and in particular to a ferrite stainless steel welding wire resistant to high temperature molten salt-liquid Cd corrosion, which is suitable for welding spent fuel dry post-processing electrolytic refining / extraction containers. To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0004] A high temperature molten salt-liquid Cd corrosion resistant ferritic stainless steel welding wire, the chemical composition of the welding wire is as follows by weight percentage:

[0005] C: <0.05%, Si: 1.5-2.5%, Ti: 0.1-0.7%, C+N: 0.02-0.07%, Al: 0.2-0.6%, Cr: 15.5-18.5%, Mo: 0.2-0.6%, the balance is Fe and unavoidable impurity elements (including one or more of O, H, B, etc.). In the chemical composition of the welding wire: P <0.01% (mass fraction), S <0.01% (mass fraction).

[0006] The welding wire can be produced by smelting in a vacuum induction furnace, or by smelting in an electric furnace plus an external refining method. The final chemical composition of the welding wire can meet the requirements within the above range.

[0007] The welding wire is used for welding of spent fuel dry post-processing electrolytic refining / extraction containers. The welding process is as follows: take a welding wire with a specification of Φ1.2mm, use tungsten inert gas welding (TIG), the joint form is butt joint, and the welding parameters are as follows: welding current 80-160A, current type / polarity direct current positive connection, welding speed 0.07-0.12m / min, arc protection uses high-purity argon gas with a purity of ≥99.995%, and the gas flow rate is 12-18L / min.

[0008] The present invention has the following advantages:

[0009] 1. Experimental verification shows that the welding wire of the present invention can be used for welding of spent fuel dry post-processing electrolytic refining / extraction containers. The welding process is simple and feasible. The commonly used tungsten inert gas welding method can be used for welding. The welding current is 120-160A, the current type / polarity is direct current positive connection, the welding speed is 0.07-0.12m / min, and the arc protection adopts high-purity argon gas with a purity of ≥99.995%, and the gas flow rate is 12-18L / min.

[0010] 2. When the ferritic stainless steel welding wire of the present invention is used to obtain a weld with excellent resistance to molten salt corrosion and liquid Cd corrosion, the welding process is stable, the defects are few, and the process performance is good.

[0011] 3. By obtaining a weld with excellent resistance to molten salt corrosion and liquid Cd corrosion in the present invention, the ferritic stainless steel welding wire can obtain a weld that meets the required performance, especially the weld has excellent resistance to molten salt corrosion and liquid Cd corrosion at 550°C.

[0012] 4. The weld obtained by welding the ferritic stainless steel welding wire resistant to high temperature molten salt-liquid Cd corrosion of the present invention has a corrosion depth of ≤10μm for 200h in a 550℃ molten salt (system is 93.8wt.% (45wt.% LiCl-55wt.% KCl)-6wt.% CeCl3-0.1wt.% SrCl2-0.1wt.% CsCl) environment (100ppm O2+18ppm H2O), and a corrosion depth of ≤4μm for 200h in a 550℃ liquid Cd corrosion environment. The room temperature yield strength of the weld is greater than 380MPa, the tensile strength is greater than 550MPa, the yield strength at 550℃ is greater than 165MPa, and the tensile strength is greater than 210MPa. The room temperature V-mouth impact energy is greater than 10.6J / cm 2

[0013] The main ideas and mechanisms of the present invention are as follows:

[0014] Ferritic stainless steel welds resistant to high temperature molten salt-liquid Cd corrosion need to have excellent resistance to molten salt corrosion and liquid metal dissolution. Ni-based materials have good resistance to molten salts, but are very easily dissolved in liquid metals, such as liquid Cd, Pb, Bi, etc.; Fe-based materials have relatively good resistance to liquid metals, but poor resistance to molten salt corrosion. Fe-based materials are selected after comprehensive evaluation, and their corrosion resistance is improved by adding corrosion-resistant elements. Therefore, the welding wire of the present invention uses Fe-based alloys, adds 17% Cr as an oxide film performance element, and adds a small amount of Si element at the same time, using its "third component" effect on the Cr oxide film to improve the film-forming ability of the oxide film and resist external corrosion. In order to further improve the corrosion resistance, the welding wire of the present invention removes Mn, Ni, and reduces austenitizing elements such as C, so as to design the matrix to be a single ferrite structure, thereby avoiding the accelerated corrosion inside the material due to multiple matrix components. However, the single ferrite leads to a coarse weld structure, resulting in poor impact toughness of the weld. Therefore, the welding wire of the present invention further adds a small amount of Ti, N and Al to form Ti (C, N). AlN acts as a grain nucleating agent, thereby refining the grains, improving the impact toughness, and playing a certain role in improving the strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of mechanical specimen and corrosion specimen sampling;

[0016] Figure 2 This is a cross-sectional photograph of the corrosion layer of Example 1 after corrosion by molten chloride salt at 550°C for 200 hours;

[0017] Figure 3 This is a cross-sectional photograph of the corrosion layer of Example 1 after being corroded in 550°C liquid Cd for 200 hours;

[0018] Figure 4 This is a cross-sectional photograph of the corrosion layer of Comparative Example 1 after corrosion by molten chloride salt at 550°C for 200 hours;

[0019] Figure 5 This is a cross-sectional photograph of the corrosion layer of Comparative Example 1 after corrosion in 550°C liquid Cd for 200 hours. DETAILED DESCRIPTION

[0020] The ferritic stainless steel welding wire of the present invention can be produced by smelting in a vacuum induction furnace, or by smelting in an electric furnace with an external refining method, as long as the final chemical composition of the welding wire can meet the requirements of the above range. In addition, the entire smelting production process and processing process of the welding wire are not significantly different from those of ordinary stainless steel welding wire, and there are no additional special technical requirements. The base material used in the welding test of the present invention is 1Cr17 ferritic stainless steel.

[0021] The following are preferred embodiments of the present invention. The welding wires in the following embodiments and comparative examples are all produced by smelting in a vacuum induction furnace. The welding wire specifications are all Φ1.2 mm. Manual tungsten inert gas arc welding (TIG) is used. The joint form is a 15 mm thick plate butt welding (the maximum thickness of the full weld tensile test specimen and the impact test specimen is 10 mm, so the welding plate thickness must be greater than 10 mm to meet the sampling size requirements), the gap at the bottom of the butt plate is 15 mm, and the single-side groove angle is 22.5°. Figure 1 The welding parameters are: welding current 140A, current type is direct current positive connection, welding speed is 0.1m / min, arc protection atmosphere is argon gas, molar purity ≥99.995%, and the flow rate of protective gas during welding is 16L / min.

[0022] After welding, the weld was subjected to post-weld heat treatment at 900°C / 1h / air cooling. The full weld corrosion specimens and mechanical specimens were tested. The sampling locations were as follows: Figure 1 As shown. Since the base material used in the welding test of the present invention is 1Cr17 ferritic stainless steel, the content of its main elements such as Fe and Cr is consistent with the welding material of the present invention, which belongs to homogeneous welding, and the bottom gap width during welding is 15mm, which further eliminates the dilution effect of the base material on the weld, and the argon arc welding has excellent protection and the element burnout rate is very small, so the chemical composition of the weld can be considered to be consistent with the composition of the welding wire.

[0023] The size of the corrosion sample is 10mm×8mm×2mm. The six surfaces of the sample were polished and chamfered with 400#, 800#, 1200#, and 2000# sandpapers in turn, and then the sample was ultrasonically cleaned with deionized water and ethanol for 10 minutes respectively, for molten salt immersion corrosion test and liquid Cd immersion corrosion test. The test used high-purity Cd particles for liquid Cd immersion test, and a mixed salt system of 93.8wt.% (45wt.%LiCl-55wt.%KCl)-6wt.%CeCl3-0.1wt.%SrCl2-0.1wt.%CsCl was used for molten salt immersion test. The high-purity Cd particles and the mixed salt were placed in a corundum crucible successively, and the samples used for molten salt immersion corrosion test and liquid Cd immersion corrosion test were suspended at corresponding heights, so that they were in the mixed salt or Cd particles respectively. Since the density of Cd is greater than that of the mixed salt and the two are immiscible, in the high-temperature molten state, the liquid Cd is at the bottom of the crucible and the mixed salt is at the top, which provides convenient conditions for carrying out molten salt immersion corrosion tests and liquid Cd immersion corrosion tests at the same time. The crucible containing the mixed salt and Cd is placed in an atmosphere furnace, and then vacuumed and Ar-O2 mixed gas (O2 content is 100.35ppm) is introduced to ensure that the oxygen content in the furnace is 100ppm O2. The water content in the furnace was measured by the dew point meter to be 18ppm. In addition, the dew point meter and oxygen analyzer were used to monitor the water and oxygen contents during the test to ensure the accuracy of the experimental atmosphere. The crucible was heated from room temperature to 550℃ in 2.5h, and the corrosion test was carried out at 550℃ for 200h.

[0024] The room temperature tensile specimen is a full weld specimen, that is, the specimen is completely located in the weld, and its length direction is parallel to the length direction of the weld. The schematic diagram of the sampling position is shown in Figure 1 The specimen size and test method for room temperature tensile testing are in accordance with GB / T 228.1-2021 "Metallic material tensile testing Part 1: Room temperature test method". The specimen size and test method for 550℃ tensile testing are in accordance with GB / T228.2-2021 "Metallic material tensile testing Part 2: High temperature test method". Both room temperature and high temperature tensile specimens are circular cross-section tests, with a parallel section diameter of 5mm and a parallel section length of 30mm.

[0025] The notch of the room temperature impact specimen is located at the center line of the weld. The specimen size and test method are in accordance with GB / T229-2020 "Charpy Pendulum Impact Test Method for Metallic Materials". See the schematic diagram of the sampling position for details. Figure 1 , the sample size is 55×10×10mm.

[0026] Example 1

[0027] The basic chemical composition of this high temperature molten salt-liquid Cd corrosion ferritic stainless steel welding wire is (weight ratio):

[0028] C: 0.041%, Si: 2.16%, Ti: 0.29%, N: 0.016%, Al: 0.3%, Cr: 16.69%, Mo: 0.4%, S: 0.0028%, P: 0.005%, and the remainder is Fe and unavoidable impurity elements (including one or more of O, H, B, etc.).

[0029] Example 2

[0030] The basic chemical composition of this high temperature molten salt-liquid Cd corrosion ferritic stainless steel welding wire is (weight ratio):

[0031] C: 0.045%, Si: 2.16%, Ti: 0.62%, N: 0.012%, Al: 0.29%, Cr: 16.65%, Mo: 0.41%, S: 0.0029%, P: 0.005%, and the remainder is Fe and unavoidable impurity elements (including one or more of O, H, B, etc.).

[0032] Example 3

[0033] The basic chemical composition of this high temperature molten salt-liquid Cd corrosion ferritic stainless steel welding wire is (weight ratio):

[0034] C: 0.041%, Si: 2.22%, Ti: 0.37%, N: 0.0028%, Al: 0.32%, Cr: 16.84%, Mo: 0.41%, S: 0.0027%, P: 0.004%, and the remainder is one or more of Fe and unavoidable impurity elements (including O, H, B, etc.).

[0035] Comparative Example 1

[0036] The basic chemical composition of this high temperature molten salt-liquid Cd corrosion ferritic stainless steel welding wire is (weight ratio):

[0037] C: 0.047%, Si: 0.017%, Ti: 0.006%, N: 0.0020%, Al: 0.003%, Cr: 16.88%, Mo: 0.2%, S: 0.0027%, P: 0.005%, and the remainder is Fe and unavoidable impurity elements (including one or more of O, H, B, etc.).

[0038] Comparative Example 2

[0039] The basic chemical composition of this high temperature molten salt-liquid Cd corrosion ferritic stainless steel welding wire is (weight ratio):

[0040] C: 0.038%, Si: 2.2%, Ti: 0.29%, N: 0.016%, Al: 0.020%, Cr: 16.96%, Mo: 0.42%, S: 0.0026%, P: 0.005%, and the remainder is Fe and unavoidable impurity elements (including one or more of O, H, B, etc.).

[0041] Comparative Example 3

[0042] The basic chemical composition of this high temperature molten salt-liquid Cd corrosion ferritic stainless steel welding wire is (weight ratio):

[0043] C: 0.013%, Si: 2.20%, Ti: 0.0018%, N: 0.026%, Al: 0.32%, Cr: 16.85%, Mo: 0.0003%, S: 0.0026%, P: 0.004%, and the remainder is Fe and unavoidable impurity elements (including one or more of O, H, B, etc.).

[0044] Comparative Example 4

[0045] The basic chemical composition of this high temperature molten salt-liquid Cd corrosion ferritic stainless steel welding wire is (weight ratio):

[0046] C: 0.040%, Si: 0.97%, Ti: 0.30%, N: 0.018%, Al: 0.32%, Cr: 16.79%, Mo: 0.42%, S: 0.0029%, P: 0.004%, and the remainder is Fe and unavoidable impurity elements (including one or more of O, H, B, etc.).

[0047] The cross-sectional depths of the welds of the above embodiments and comparative examples at 550°C / 200h molten salt corrosion and liquid Cd corrosion are shown in Table 1, the room temperature tensile and impact properties are shown in Table 2, and the 550°C tensile properties are shown in Table 3.

[0048] Table 1 Cross-sectional depth of weld seam 550℃ / 200h molten salt corrosion and liquid Cd corrosion in the examples and comparative examples

[0049] Molten salt corrosion depth (μm) Liquid Cd corrosion depth (μm) Design Specifications ≤10 ≤4 Example 1 9 3.2 Example 2 9.3 3.8 Example 3 8.9 4 Comparative Example 1 43 7.2 Comparative Example 2 9.2 3.6 Comparative Example 3 8.8 2.9 Comparative Example 4 18 4.8

[0050] Table 2 Test results of room temperature tensile strength and impact energy of welds in embodiments and comparative examples

[0051]

[0052]

[0053] Table 3 550℃ tensile strength test results of the welds of the embodiments and comparative examples

[0054]

[0055] The weld obtained by the welding wire designed by the present invention has the following performance design indicators: the corrosion depth is ≤10μm for 200h in a 550℃ molten salt (system is 93.8wt.% (45wt.% LiCl-55wt.% KCl)-6wt.% CeCl3-0.1wt.% SrCl2-0.1wt.% CsCl) environment (100ppm O2+18ppm H2O), and the corrosion depth is ≤4μm for 200h in a 550℃ liquid Cd corrosion environment. Mechanical properties: after heat treatment, the weld has a room temperature yield strength of >380MPa, a tensile strength of >550MPa, a 550℃ yield strength of >165MPa, and a tensile strength of >210MPa. Room temperature impact toughness >10.6J / cm 2 From Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, it can be seen from Tables 1 to 3 that:

[0056] Embodiments 1, 2, and 3 adopt the chemical composition of the welding wire designed by the present invention, and the composition range meets the preferred composition of the welding material described in claim 1 or 2. The performance meets the performance design requirements of the present invention, the welding process is stable, the X-ray non-destructive detection defects are small, and the process performance is good.

[0057] In Comparative Example 1, the contents of Si, Ti and Al are not within the scope of the technical solution of the present invention. The Si element mainly plays a role in improving the film-forming ability of the protective oxide film. Therefore, the molten salt corrosion resistance and liquid Cd corrosion resistance of the weld do not meet the design requirements of the present invention; Ti and Al play a role in refining the grains and improving the impact toughness and strength. Therefore, the room temperature yield strength, room temperature tensile strength, room temperature impact toughness and 550°C yield strength do not meet the design requirements of the present invention.

[0058] In Comparative Example 2, the Al content is not within the scope of the technical solution of the present invention, and the room temperature yield strength, room temperature tensile strength, and room temperature impact toughness of the weld do not meet the design requirements of the present invention.

[0059] In Comparative Example 3, the contents of Ti and Mo are not within the scope of the technical solution of the present invention, wherein Mo plays a role of solid solution strengthening and can improve the strength. Therefore, the room temperature yield strength, room temperature tensile strength, room temperature impact toughness, 550°C yield strength and 550°C tensile strength of the weld do not meet the design requirements of the present invention.

[0060] In Comparative Example 4, the Si content is not within the scope of the technical solution of the present invention, and the weld's molten salt corrosion resistance and liquid Cd corrosion resistance do not meet the design requirements of the present invention.

[0061] The above embodiments only express several implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A high temperature molten salt-liquid Cd corrosion resistant ferritic stainless steel welding wire, characterized in that: The chemical composition of the welding wire is as follows by weight percentage: C: ≤0.05%, Si: 1.5-2.5%, Ti: 0.1-0.7%, C+N: 0.02-0.07%, Al: 0.2-0.6%, Cr: 15.5-18.5%, Mo: 0.2-0.6%, the balance is Fe and unavoidable impurity elements.

2. The ferritic stainless steel welding wire according to claim 1, characterized in that: Measured in percentage by weight, the chemical composition of the welding wire is preferably as follows: C: 0.02-0.05%, Si: 1.5-2.5%, Ti: 0.2-0.6%, N: 0.01-0.02%, Al: 0.2-0.4%, Cr: 16-18%, Mo: 0.2-0.6%, and the remainder is Fe and unavoidable impurity elements.

3. The ferritic stainless steel welding wire according to claim 1 or 2, characterized in that: The chemical composition of the welding wire is: P < 0.01% (mass fraction), S < 0.01% (mass fraction).

4. An application of the welding wire according to any one of claims 1 to 3, characterized in that: The welding wire is used for melting welding of spent fuel dry reprocessing electrolytic refining / extraction containers (ferritic stainless steel) or for welding components in high-temperature molten salt and liquid Cd coupled corrosion environments.

5. The use according to claim 4, characterized in that: The welding process of the welding wire is as follows: take a welding wire with a specification of Φ1.2-2.0mm (such as: Φ1.2mm or Φ2.0mm), use tungsten inert gas welding (TIG), the joint form is butt joint, the welding parameters are: welding current 80-160A, current type is direct current positive connection, welding speed 0.07-0.12m / min, arc protection atmosphere is argon gas, molar purity ≥99.995%, and the protective gas flow rate during welding is 12-18L / min.

6. The use according to claim 4 or 5, characterized in that: The weld is resistant to corrosion at 550℃ in a molten salt (system is 93.8wt.% (45wt.% LiCl-55wt.% KCl)-6wt.% CeCl3-0.1wt.% SrCl2-0.1wt.% CsCl) environment (100ppm O2+18ppm H2O) for 200h with a depth of ≤10μm, and in a 550℃ liquid Cd corrosion environment for 200h with a depth of ≤4μm; Mechanical properties: After heat treatment, the room temperature yield strength of the weld is >380MPa, the tensile strength is >550MPa, the yield strength at 550℃ is >165MPa, the tensile strength is >210MPa; the room temperature impact toughness is >10.6J / cm 2 .

Citation Information

Patent Citations

  • Metal powder-cored type nitrogen austenite stainless steel flux-cored wire and method for manufacturing same

    CN103042321A

  • Molten salt corrosion resistant nickel-based superalloy with excellent performance

    CN103966476A

  • Welding flux for molten salt corrosion resistant nickel-base superalloy fusion welding

    CN106077997A

  • Iron base high-temperature alloy welding wire

    CN110405380A

  • High-alloy steel wear-resistant flux-cored wire and preparing method thereof

    CN110788520A